Pengaruh Pupuk Bokashi Terhadap Pertumbuhan Mentimun (Cucumis sativus L.) si Desa Sukawening, Kabupaten Bogor, Jawa Barat - Elsa Amelya Fitriany; Zaenal Abidin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Sukawening Village is a village dominated by farming communities. Agricultural products are obtained by farmers in this village still unoptimal. One contributing factor is the quality of fertilizer used. Bokashi fertilizer is a fertilizer that is rich in nutrient content and can increase significant agricultural yields. Therefore, the SUIJI 2020 students in Sukawening Village educated farmers on how to make bokashi fertilizer. The purpose of education in making bokashi fertilizer for farmers is that farmers can make bokashi fertilizer independently and produce more agricultural yields so that the agricultural benefits obtained are greater. The effect of bokashi fertilizer on plant growth will be discussed in this journal. The method used is interview with farmer in Sukawening Village and IPB University students that focused of plantation engineering as well as literature studies from relevant journals. Data from interview will compare with data from literature and then make the concusion. The results of this study were application of bokashi fertilizer to plants give significant effect seen with high fruit weight. Based on a literature, cucumber plants using bokashi fertilizer mixed with NPK fertilizer produces a weight of 88.93 tons /ha while based on interviews, cucumber plants in Sukawening Village using manure mixed with NPK fertilizer produce fruit with minimum weight 30 tons/ha . Microorganisms and organic compounds in Bokashi fertilizer influence the increase nutrients so that it supports plant growth. Bokashi fertilizer has potential to increase agricultural output in Sukawening Village and hoped this fertilizer can be used sustainably. Key word: bokashi fertilizer, microorganism, nutrient, weight of fruit